2016
DOI: 10.1103/physrevb.94.195101
|View full text |Cite
|
Sign up to set email alerts
|

Europium mixed-valence, long-range magnetic order, and dynamic magnetic response in EuCu2(SixGe1x)2

Abstract: In mixed-valence or heavy-fermion systems, the hybridization between local f orbitals and conduction band states can cause the suppression of long-range magnetic order, which competes with strong spin fluctuations. Ce-and Yb-based systems have been found to exhibit fascinating physical properties (heavy-fermion superconductivity, non-Fermi-liquid states, etc.) when tuned to the vicinity of magnetic quantum critical points by use of various external control parameters (temperature, magnetic field, chemical comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 59 publications
1
14
0
2
Order By: Relevance
“…По этой же причине электрическое поле лигандов, которое зависит от расстояния до них, не должно было бы расщеплять основные уровни этих ионов. На самом же деле, как ранее нами указывалось [1], в экспериментах было обнаружено и объяснено в теории, что небольшие расщепления существуют [20][21][22][23][24][25]. Небольшое расщепление (порядка 10 −4 −10 −3 базовой величины) имеет место даже для кубической симметрии кристалла, не говоря о симметриях более низкого порядка, тетрагональной или тригональной.…”
Section: Discussionunclassified
“…По этой же причине электрическое поле лигандов, которое зависит от расстояния до них, не должно было бы расщеплять основные уровни этих ионов. На самом же деле, как ранее нами указывалось [1], в экспериментах было обнаружено и объяснено в теории, что небольшие расщепления существуют [20][21][22][23][24][25]. Небольшое расщепление (порядка 10 −4 −10 −3 базовой величины) имеет место даже для кубической симметрии кристалла, не говоря о симметриях более низкого порядка, тетрагональной или тригональной.…”
Section: Discussionunclassified
“…По этой же причине электрическое поле лигандов, которое зависит от расстояния до них, не должно было бы расщеплять основные уровни этих ионов. На са-мом же деле, как было обнаружено в экспериментах и объяснено в теории, небольшие расщепления суще-ствуют [17][18][19][20][21][22]. Небольшое расщепление (∼ 10 −4 −10 −3 базовой величины) имеет место даже для кубической симметрии кристалла, не говоря о симметриях более низкого порядка -тетрагональной или тригональной.…”
Section: Discussionunclassified
“…The authors have observed large Sommerfeld coefficient γ exceeding 900 mJ/mol K 2 for Cu and Ga doped in antiferromagnetic heavy fermion system U 2 Zn 17 (Svanidze et al, 2018). There is a recent experimental report of the presence of long range magnetic order and dynamic magnetic response in Europium based mixed valence system (Nemkovski et al, 2016).…”
Section: Introductionmentioning
confidence: 98%